Smart Mobility Opportunities and Conditions - Staricco, Luca (TeMA - Journal of Land Use, Mobility and Environment, 2013)
Smart mobility is often presented, in the strategies for smart cities that public institutions and private big players are promoting, as one of the main options, if not “the option”, to pursue more sustainable transport systems. Most of the opportunities of smart mobility are related to technological innovations for managing and organizing trips and traffic and for improving the environmental efficiency of vehicles; but the impacts of these innovations, in particular over the long term, depend on how they are embedded by the users in their daily activities and practices. These “boundary conditions” are often disregarded, just as they generally concern not a technological dimension, but the psychological-cognitive and socio-cultural domain. The paper tries to analyze these boundary conditions, which opportunities they can support and which risks can emerge if they are not fulfilled. It also tries to argue, by some experiences from the case of Turin (an Italian city that is considered at the cutting edge of smart mobility), why at the heart of smart mobility policies there should be citizens instead of technologies, and why these policies should be supported and integrated by other measures and policies (for transports, urban planning, education and so on) in order to influence the behavior and the choices of these citizens.